Programmed death ligand 1 expression in triple‐negative breast cancer is associated with tumour‐infiltrating lymphocytes and improved outcome. Issue 1 (13th January 2016) - Beckers, Rhiannon K; Selinger, Christina I; Vilain, Ricardo; Madore, Jason; Wilmott, James S; Harvey, Kate; Holliday, Anne; Cooper, Caroline L; Robbins, Elizabeth; Gillett, David; Kennedy, Catherine W; Gluch, Laurence; et al.
Abstract : Aims: Triple‐negative breast cancer (TNBC) patients generally have a poor outcome; there is a pressing need to identify more effective therapeutic strategies. Clinical trials targeting programmed death 1/programmed death ligand 1 (PD1/PDL1) in melanoma and non‐small‐cell lung cancer have reported high response rates, and tumoral PDL1 expression has been suggested as a potential biomarker to enrich for patient response to these treatments. There are only very limited data to date reporting the expression of PDL1 in TNBC. Methods and results: PDL1 immunohistochemistry was performed on 161 primary TNBCs and assessed in the tumour as well as immune cells in the stromal compartment. PDL1 expression was very common in TNBC, expressed in the tumour cell membrane (64%), cytoplasm (80%) and stromal (93%) cellular compartments. Cytoplasmic tumoral expression of PDL1 was associated with a lower risk of breast cancer‐specific death [hazard ratio (HR) 0.45, P = 0.035] while stromal PDL1 expression was associated with a lower rate of deaths from all causes (HR 0.305, P = 0.0042). Membranous expression of PDL1 was not associated with outcome. While both PDL1 expression and tumour‐infiltrating lymphocytes were associated with a better outcome, only lymphovascular invasion and high tumour‐infiltrating lymphocytes were independently prognostic for breast cancer‐specific death. Conclusion: While PDL1 expression is frequent in TNBC, it was not independently prognostic. There were differences in outcome depending on the cellular compartment of PDL1 expression. These data provide further impetus for investigating the utility of immune checkpoint therapies in TNBC, given the clinical significance of tumour‐infiltrating lymphocytes (TILs) and PDL1 expression in this cohort.